Meeting people - Barlow, Alex.; Hill, Marji; Gilbert, Kevin, 1933-1993. (South Melbourne : Macmillan, 1987)
For children; Biographical sketches of G. Stow, A. Mullett, H. Sculthorpe, I. Clayton; R. Bostock, K. Colbung; early life, schooling, significant experiences, present situation, occupation.
Includes index.
For primary school students.
White, K. Bibliography of Australian children's books
Keywords: Aboriginal Australians -- Cultural assimilation -- Juvenile literature; Wiradjuri people (D10) (NSW SI55-07); Education; History - Biographies - Indigenous; Literature and stories - Juvenile; Kurnai / Gunai people (S68) (Vic SJ55); Leeton (SW NSW SI55-10); Bairnsdale (E Vic Gippsland SJ55-07); Cairns (NE Qld SE55-02); Badu / Mulgrave Island (Qld TSI SC54-11); Australia